PENGEMBANGAN MEDIA BOWLING ANGKA TERHADAP KEMAMPUAN BERHITUNG ANAK USIA DINI 5-6 TAHUN DI TK IT AL-KAHFI DESA KEMU KECAMATAN PULAU BERINGIN - Ramadhanty, Nora; Hamzah, Amir; Cindrya, Elsa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The purpose of this study was to develop valid, practical, and effective number bowling media to improve children's counting skills at IT Al-Kahfi Kindergarten, Kemu Village. The research method is research and development with the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The one to one trial stage amounted to 5 students and a small group trial with 10 students. Data collection techniques using observation, questionnaires, interviews and documentation. The data analysis technique uses validity test, practical test, and effectiveness test. The results showed the validity of material experts 87.5 very valid category and media experts 92.5 very valid category. Practicality test of number bowling media based on teacher response questionnaire, 86.6 very practical category and in the student response trial using one to one 91.28 categorized as very practical and 89.63 categorized as very practical in the small group trial. The effectiveness test is seen from the hypothesis test using the t-test, obtained tcount = 103.439 while for ttable = 2.313. So it can be concluded that tcount> ttable then Ha is accepted and Ho is rejected. It is concluded that the number bowling media to improve children's counting skills is valid, practical, and effective to use in learning.